Integration Examination in the Russian Federation. Three years of experience and research: Success or failure? - Anzhela V. Dolzhikova; Marina N. Kunovski (Peoples' Friendship University of Russia (RUDN University), 2018)
The 3-module Integration Examination, incorporating Russian Language, History and the Basics of Law tests, is a mandatory integration requirement for immigrants in Russia. Integration tests and educational courses are only a few examples of the new 'civic integration policies' used all over the world to promote common values for newcomers. Through the present study, the authors address the question of whether these requirements facilitate the migrants' integration process. In doing so, they examine the impact of the Integration Exam in Russia as one of its integration policy strategies. The paper draws on surveys to explore the attitude towards the Integration Exam among different categories of migrants. The research is supported by the all-Russia 2015-2017 Integration Exam statistics. The authors reveal causal relationships between language proficiency and integration. The results presented in the paper indicate that most migrants support the idea of the Integration Exam and demonstrate understanding of the importance of civic integration. The level of integration correlates with the purpose of migration, which is reflected in the Integration Exam's level structure. The findings presented in the article help explore the Exam's perspectives, facilitate better-addressed education programmes, and discuss legislative initiatives affecting Russia's State Migration Policy.